Enhancement of Physical Appearance, Skin Permeation, and Odor Reduction Using Liposome of Hydrolyzed Salmon Collagen for Cosmetic Products - Thanaporn Amnuaikit; Rajeev Shankar Rajagopal; Krisana Nilsuwan; Soottawat Benjakul (Scientifica)
Hydrolyzed collagen (HC) derived from salmon (Oncorhynchus nerka) skin possesses properties that can nourish the skin, and it is one of the active ingredients used in cosmeceutical products for moisturizing the facial skin. However, HC solution gives off a fishy odor and it is gray in color that makes the product unacceptable for cosmetic purposes. This study aimed to use liposome-encapsulated hydrolyzed salmon collagen to improve its physical appearance, skin permeation, and eliminate the fishy odor. Two percent of HC and vitamin B3 (VitB3) were used as active ingredients to incorporate into liposomes. Phosphatidylcholine, cholesterol, and Tween 80 at a suitable weight ratio of 8 : 2 : 1 produced nano-sized vesicles (170.6 ± 0.70 nm) with the highest percentage of entrapment efficiency (95.72 ± 2.00%) of VitB3 and (49.63 ± 1.74%) of HC. Skin permeation and odor detection of the HC-VitB3 liposome were studied using Franz’s diffusion cell and gas chromatography, respectively, and compared with HC-VitB3 solution. Subsequently, facial serums were formulated using HC-VitB3 liposomes and HC-VitB3 solutions, and a product satisfaction test was conducted with 100 volunteers to determine their preferred product. The results of the studies of HC-VitB3 liposome serum showed improved formulation appearance, enhanced skin permeation, and better odor elimination compared to the HC-VitB3 serum. Furthermore, seventy-three volunteers in the product satisfaction test preferred and selected the liposomal serum for its superior scent. From all the experimental results, it could be seen that liposomes can help increase skin penetration, and undesirable odors and colors can be masked by the appropriate lipid bilayer structure of liposomes.